The Effect of Reward Policy and Work Motivation on Employee Performance at PT Natura Nuswantara Nirmala - Fauziah, Annisa Frisca; Adhanurrizqi, Nafiisah; Rekatami, Tanri; Arpan, Harizul; Saputra, Riagung (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on the results of the analysis carried out in this study, the results show that awards have a significant effect on the performance of employees of PT. Natura Nuswantara Nirmala with the results indicated by a significance value of t of 0.025 which is smaller than a = 0.05 (0.025 <0.05) with a regression coefficient of 0.343. Work motivation has a significant effect on the performance of employees of PT. Natura Nuswantara Nirmala with results indicated by a significance value of t of 0.000 which is smaller than a = 0.05 (0.013 <0.05) with a regression coefficient of 0.535. Appreciation and work motivation simultaneously have a significant effect on the performance of employees of PT. Natura Nuswantara Nirmala with results indicated by a significance value of F of 0.000 less than a = 0.05 (0.000 <0.05) and is able to contribute to the employee performance variable of 0.800 or 80%. The remaining 20% ​​is influenced by other variables not listed and examined in this study.